Children with low working memory and children with ADHD: same or different? - Holmes, Joni; Hilton, Kerry A.; Place, Maurice; Alloway, Tracy P.; Elliott, Julian G.; Gathercole, Susan E. (Frontiers in Human Neuroscience, 2014)
The purpose of this study was to compare working memory (WM), executive function, academic ability and problem classroom behaviors in children aged 8 to 11 years who were either identified via routine screening as having low WM, or had been diagnosed with ADHD. Standardised assessments of WM, executive function and reading and mathematics were administered to 83 children with ADHD, 50 children with low WM and 50 typically developing children. Teachers rated problem behaviors on checklists measuring attention, hyperactivity/impulsivity, oppositional behavior, and difficulties associated with executive function in the classroom. The ADHD and low WM groups had highly similar WM and executive function profiles, but were distinguished in two key respects: children with ADHD had higher levels of rated and observed impulsive behavior, and children low WM had slower response times. Possible mechanisms for these common and distinct deficits are discussed.